Recent advances in enhancing the sensitivity of electrophoresis and electrochromatography in capillaries and microchips (2016–2018). Issue 1 (6th November 2018) - Breadmore, Michael C; Grochocki, Wojciech; Kalsoom, Umme; Alves, Mónica N.; Phung, Sui Ching; Rokh, Masoomeh Tehrani; Cabot, Joan M.; Ghiasvand, Alireza; Li, Feng; Shallan, Aliaa I.; Keyon, Aemi S. Abdul; Alhusban, Ala A.; et al.
Abstract: One of the most cited limitations of capillary and microchip electrophoresis is the poor sensitivity. This review continues to update this series of biannual reviews, first published in Electrophoresis in 2007, on developments in the field of online/in‐line concentration methods in capillaries and microchips, covering the period July 2016–June 2018. It includes developments in the field of stacking, covering all methods from field‐amplified sample stacking and large‐volume sample stacking, through to isotachophoresis, dynamic pH junction, and sweeping. Attention is also given to online or in‐line extraction methods that have been used for electrophoresis.